2005
DOI: 10.3171/spi.2005.2.2.0099
|View full text |Cite
|
Sign up to set email alerts
|

Sciatica of nondisc origin and piriformis syndrome: diagnosis by magnetic resonance neurography and interventional magnetic resonance imaging with outcome study of resulting treatment

Abstract: Object. Because lumbar magnetic resonance (MR) imaging fails to identify a treatable cause of chronic sciatica in nearly 1 million patients annually, the authors conducted MR neurography and interventional MR imaging in 239 consecutive patients with sciatica in whom standard diagnosis and treatment failed to effect improvement. Methods. After performing MR neurography and intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
229
1
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(248 citation statements)
references
References 49 publications
4
229
1
14
Order By: Relevance
“…• Gluteal trauma in the sacroiliac or gluteal areas (possibly several years previously) 13,22,33 • Predisposing anatomic variants 4,5,7,14,15,40,41 • Myofascial trigger points 7,20,38,39,42 • Hypertrophy and spasm of the piriformis muscle 14,18,[43][44][45] • Secondary to laminectomy 13,38,39,43,[46][47][48][49][50] • Abscess, 51 hematoma, 52,53 myositis, 54 bursitis of the piriformis muscle, 55 neoplasms in the area of the infrapiriform foramen, 56 colorectal carcinoma, 57 neurinoma of the sciatic nerve, 18 episacroiliac lipoma 50 • Intragluteal injection 58 • Femoral nailing 18 • Myositis ossificans of the piriformis muscle 3,59 • Klippel-Trénaunay syndrome 18 Table 2 Differential diagnosis of piriformis syndrome…”
Section: Clinical Presentationmentioning
confidence: 99%
“…• Gluteal trauma in the sacroiliac or gluteal areas (possibly several years previously) 13,22,33 • Predisposing anatomic variants 4,5,7,14,15,40,41 • Myofascial trigger points 7,20,38,39,42 • Hypertrophy and spasm of the piriformis muscle 14,18,[43][44][45] • Secondary to laminectomy 13,38,39,43,[46][47][48][49][50] • Abscess, 51 hematoma, 52,53 myositis, 54 bursitis of the piriformis muscle, 55 neoplasms in the area of the infrapiriform foramen, 56 colorectal carcinoma, 57 neurinoma of the sciatic nerve, 18 episacroiliac lipoma 50 • Intragluteal injection 58 • Femoral nailing 18 • Myositis ossificans of the piriformis muscle 3,59 • Klippel-Trénaunay syndrome 18 Table 2 Differential diagnosis of piriformis syndrome…”
Section: Clinical Presentationmentioning
confidence: 99%
“…7,8 The MA is associated with a hyperintense T2 signal-intensity alteration in tissues densely composed of collagen, was first observed in tendons and ligaments, and was later reported also to occur in peripheral nerves. [9][10][11][12] It is conceived as a T2 signal-intensity increase related to the suppression of dipole-dipole interactions of the hydrogen protons bound to quasicrystalline structures such as tropocollagen, the triple-helical main compound of various types of fibrillary collagen.…”
mentioning
confidence: 99%
“…Filler and colleagues demonstrated that unilateral T2 high intensity of the sciatic nerve at the sciatic notch and asymmetry of the piriformis muscle on the MRI are the findings specific to piriformis syndrome (Filler et al, 2005). No abnormalities of the sciaticinnervated muscles are seen on the MRI.…”
Section: Sciatic Nervementioning
confidence: 99%